Perspective and challenges in electrochemical approaches for reactive CO2 separations - Burcu Gurkan (Elsevier, 2021)
Summary: The desire toward decarbonization and renewable energy has sparked research interests in reactive CO2 separations, such as direct air capture that utilize electricity as opposed to conventional thermal and pressure swing processes, which are energy-intensive, cost-prohibitive, and fossil-fuel dependent. Although the electrochemical approaches in CO2 capture that support negative emissions technologies are promising in terms of modularity, smaller footprint, mild reaction conditions, and possibility to integrate into conversion processes, their practice depends on the wider availability of renewable electricity. This perspective discusses key advances made in electrolytes and electrodes with redox-active moieties that reversibly capture CO2 or facilitate its transport from a CO2-rich side to a CO2-lean side within the last decade. In support of the discovery of new heterogeneous electrode materials and electrolytes with redox carriers, the role of computational chemistry is also discussed.